Investigation of disc brake interface strain distributions using Fibre Bragg Grating sensors - Wang, Zicheng (Cranfield University, 2022)
The processes occurring at the friction brake interface are complex due to the high interface pressure, and heat and wear, which change continually and are governed by the thermo-elastic instability phenomenon. Complexities in modelling are mainly related to the inability to establish all necessary material properties. Experimental investigations, on the other hand, are difficult due to the challenging working environment and limited space, whilst the sensors used should not disturb the very process that is being monitored. The Thesis uses optical Fibre Bragg Grating (FBG) strain sensors, having a small diameter of order 250 µm and temperature resistance of several hundred degrees. The brake pads are modified by creating shallow and narrow grooves in which the optical fibre sensors are installed. In such a manner, the strains are measured in the close proximity to the friction surface, with minimum modifications and influence on the interface contact. Two special rigs were used, one for static and quasi-dynamic testing, and the other for dynamic brake applications, employing the complete brake assembly and accurately controlled test environment. The static loading phase involved step-wise hydraulic pressure changes (0bar to 120bar) and variations (pressure applied to the piston sets differed by ±10bar) to understand the brake pad interface performance, while the quasi-dynamic measurement phase involved the application of torque levels (200Nm, 600Nm & 1000Nm) at varying hydraulic pressure levels (40bar, 80bar and 120bar). The measurements confirmed the FBG sensors’ suitability for interface strain measurements, with high level of accuracy and repeatability, within a wide range of brake operating conditions. Comparisons with finite element (FE) analyses in the static and quasi-dynamic conditions showed very good agreement. In the dynamic phase, the disc brake system is exposed to a (approx.) 50rpm disc rotational speed and 30bar applied hydraulic pressure, which represents the first reported attempt to apply the optical sensing technique on a disc brake under dynamic loading conditions. FBG sensors were able to follow the fast-changing strain distributions at the pad/disc interface, and a means of correcting the influence of temperature on the sensor response was implemented. The possibility of direct measurement and monitoring of a truly dynamic change in the strain distributions at the entire pad frictional surface during braking lays the foundations for dynamic monitoring of pressure and temperature distributions at the brake pad frictional interface.
Tirovic, Marko - Associate Supervisor
Keywords: Interface Strain Distributions; Fibre Bragg Grating (FBG); Finite Element Analysis (FEA); Interface Pressure Distributions (IPD); Disc Brake; static testing; quasi-dynamic testing